If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -4) + 3(3x + 5) = 33 Reorder the terms: 2(-4 + 2x) + 3(3x + 5) = 33 (-4 * 2 + 2x * 2) + 3(3x + 5) = 33 (-8 + 4x) + 3(3x + 5) = 33 Reorder the terms: -8 + 4x + 3(5 + 3x) = 33 -8 + 4x + (5 * 3 + 3x * 3) = 33 -8 + 4x + (15 + 9x) = 33 Reorder the terms: -8 + 15 + 4x + 9x = 33 Combine like terms: -8 + 15 = 7 7 + 4x + 9x = 33 Combine like terms: 4x + 9x = 13x 7 + 13x = 33 Solving 7 + 13x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 13x = 33 + -7 Combine like terms: 7 + -7 = 0 0 + 13x = 33 + -7 13x = 33 + -7 Combine like terms: 33 + -7 = 26 13x = 26 Divide each side by '13'. x = 2 Simplifying x = 2
| 3x=7x/10 | | 3x=7x/2 | | 3x=10(7x) | | (4x+15)=180 | | 2(12x^2-x)=15 | | (300*x)+3y=6250 | | x^2+y^2+2x+2y-2=0 | | X/3-8-2 | | 3p-3/5*4p^2/p^2-p | | 44+78(5x+3)=180 | | 2x^3-28x^2-48x=0 | | P(2)=x^4-2x^2+5x+6 | | 56-2x=36 | | 3(-8)-1=-19 | | 1.56g+0.95=0.5k | | P(x)=x^4-2x^2+5x+6 | | X^3-2x^2+3x-3=0 | | 0.1-x/x=0.56 | | B/5=b-13/6 | | 4x^3-58x=0 | | X+5-2x=8 | | -3x+3=-2+6x | | 16x+9=12x+21 | | 10n^2=n^2+16 | | 45x+85=300 | | 23+(-78)= | | -2(2y+3)+2=0 | | 16+2v+3v-9=6v+12-v-5 | | y+6.2=2.4 | | 5(8F)+4(9-F)+37= | | 0.1x/x=0.56 | | f(x)=x^2+3x-88 |